Absurdism: Aesthetic category in the story “Un grito” (1947) by Carlos Salazar Herrera - Huertas-Arredondo, Kimberly (2024)
The purpose of this article is to analyze the features of Camusian absurdism present in the short story “Un grito” (“A Scream”) (1947), by the Costa Rican writer Carlos Salazar Herrera. Specifically, it will focus on the expression of the absurdism and what this category implies in the configuration of the textual interweaving of the story. As theoretical-methodological references, The Myth of Sisyphus (1942) by the Algerian-French writer Albert Camus, and the theory of intertextuality by Julia Kristeva (1978). In this analysis, it was proved that in the text under study there are elements of the absurdism that demonstrate the influence of Camusian thought in Salazar Herrera’s storytelling.